2016
DOI: 10.1103/physreve.93.033126
|View full text |Cite
|
Sign up to set email alerts
|

Development of tip-splitting and side-branching patterns in elastic fingering

Abstract: Elastic fingering supplements the already interesting features of the traditional viscous fingering phenomena in Hele-Shaw cells with the consideration that the two-fluid separating boundary behaves like an elastic membrane. Sophisticated numerical simulations have shown that under maximum viscosity contrast the resulting patterned shapes can exhibit either finger tip-splitting or side-branching events. In this work, we employ a perturbative mode-coupling scheme to get important insights into the onset of thes… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(1 citation statement)
references
References 37 publications
0
1
0
Order By: Relevance
“…Another strategy is to use a non-Newtonian fluid as one of the fluids, where the anisotropy is an intrinsic property of the medium itself. Theoretical work and numerical simulations have suggested that the local decrease in viscosity in front of the fingertip occurring in shear-thinning viscoelastic fluids can suppress tip splitting by introducing a preferred growth direction (28)(29)(30)(31). Experimentally, intrinsically anisotropic thermotropic liquid crystals (TLCs) have been used as the displaced fluid (32).…”
Section: Introductionmentioning
confidence: 99%
“…Another strategy is to use a non-Newtonian fluid as one of the fluids, where the anisotropy is an intrinsic property of the medium itself. Theoretical work and numerical simulations have suggested that the local decrease in viscosity in front of the fingertip occurring in shear-thinning viscoelastic fluids can suppress tip splitting by introducing a preferred growth direction (28)(29)(30)(31). Experimentally, intrinsically anisotropic thermotropic liquid crystals (TLCs) have been used as the displaced fluid (32).…”
Section: Introductionmentioning
confidence: 99%